Physical Activity and Inflammatory Bowel Diseases: Evidence from Animal Models - Sobieszek, Kamil A.; Idzik, Patrycja (Quality in Sport, 2025)
Background: Inflammatory bowel diseases (IBD), including Crohn’s disease and ulcerative colitis, are chronic disorders marked by immune dysregulation, oxidative stress, and barrier dysfunction. Physical activity has systemic anti-inflammatory and antioxidant effects, yet mechanisms influencing intestinal inflammation remain unclear. Animal models of colitis provide key insights. Aim: To summarize preclinical evidence on how exercise affects IBD, focusing on immune, oxidative, and microbiota-related mechanisms in animal models. Methods: A narrative review of studies up to September 2025 was conducted using PubMed, Scopus, and Web of Science. Search terms included “exercise,” “physical activity,” “colitis,” “IBD,” “DSS,” and “TNBS.” Eligible studies used rodent models of induced colitis with defined exercise protocols. Data on animal type, induction method, exercise parameters, and outcomes were analyzed qualitatively. Results: Moderate physical activity consistently attenuated colonic inflammation, oxidative damage, and permeability. Exercise reduced TNF-α, IL-1β, and IL-6, while increasing IL-10 expression. It activated Nrf2 signaling, enhancing antioxidant enzymes (SOD, catalase), and improved gut microbiota diversity. In contrast, high-intensity or forced exercise aggravated mucosal injury, oxidative stress, and cytokine imbalance, indicating a dose-dependent effect. Conclusions: Evidence from animal studies shows that regular, moderate exercise protects against experimental colitis through immune, oxidative, and microbial modulation. These findings highlight exercise as a potential adjunctive approach for IBD prevention and management, though optimal regimens for clinical translation require further study.